Куница каменная (Martes foina Erol.) в Одессе - Волянский, Ю.Е. (Вестник зоологии, 1967)
In last years the stone marten (Manes foina Erx 1.) was found in various parts of Odessa, where it inhabits the garrets of the houses, sheds and storehouses. The stone marten feeds on vegetable food (fruits and seeds of various plants) and small birds, rodents and insects. Settling close to a man, the stone morten became a real synantropic animal.